Optical manipulation of animal behavior using a ruthenium-based phototrigger - Rojas Pérez, Yeraldith (2019)
A visible-light activatable caged compound based on a ruthenium-polypyridine complex was used to elicit the feeding response of the freshwater cnidarian Hydra vulgaris. The phototrigger delivers l-arginine in a clean reaction under irradiation with blue or green light. The synthesis, characterization and application mode of this caged arginine are described. A combination of fiber-optics setup and a high absorbance medium allows the precise control of uncaging in the submillimetric range, needed to address the zone where activation takes place.